Odpowiedzi

2009-12-09T20:48:16+01:00
A) (
4x-5y =-4
-2X+3y = 1,1 /*2

4x-5y =-4
-4x+6y =2,2
-----------------dodajemy
y=-1,8

-2x+3y = 1,1
2x=3y-1,1
x= 3/2y -0,55
x=3/2*(-1,8)-0,55
x=-2,7-0,55
x=-3,25
------------------------------
B)
3x -2y =-12 /*(-2)
2x -5y =-19 /*3

-6x+4y=24
6x-15y=-57
------------------dodajemy
-11y=-33 /*(-1)
11y=33
y=33/11
y=3

3x -2y =-12
3x=2y-12
x=2/3y-4
x=2/3*3-4
x=-2
2009-12-09T21:00:30+01:00
A)
4x-5y=-4
-2x+3y1,1/*2

4x-5y=-4
-4x+6y=2,2
____________
y=1,8

4x-5*1,8=-4
y=1,8

4x=-4+9
y=1,8

4x=5/4
y=1,8

x=1,25
y=1,8

b)
3x-2y=-12/*5
2x-5y=-19/*(-2)

15x-10y=-60
-4x+10y=38
_____________
9x=22/:9
x=2,4

3*2,4-2y=-12
x=2,4

2y=-12-7,2
x=2,4

2y=19,2/:2
x=2,4

y=9,6
x=2,4